CONTRA gη-CONTINUITYIN TOPOLOGICAL SPACES - et al., D. Subbulakshmi (International Journal of Advanced Science and Technology, 2019)
In this paper a new class of functions namely contra gη-continuous in the light of gη-continuous in topological spaces is introduced. Further some of their characterizations are investigated